2012
DOI: 10.1007/s00705-011-1215-5
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of hepatitis B surface antigen and anti-HBs in Chinese chronic hepatitis B virus patients relating to genotype C and mutations in the S and P gene reverse transcriptase region

Abstract: We aimed to determine the prevalence of the coexistence of HBsAg and anti-HBs and to analyze the clinical and virological features of infection, including amino acid (aa) patterns of the S gene and reverse transcriptase (RT) region in Chinese chronic hepatitis B (CHB) patients. Fifty-four (2.90%) CHB patients who were positive for both HBsAg and anti-HBs were tested, and sequences were obtained from 52 of them as well as 48 patients from a control group. S gene and RT region sequences were amplified and sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
48
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(65 citation statements)
references
References 25 publications
(51 reference statements)
14
48
3
Order By: Relevance
“…Therefore, routine screening for HBV in schizophrenia patients is advocated, and HBV as well as hepatitis A immunization is recommended. In this study, 38.1% of HBsAg-positive patients showed coexistence of HBsAb, which was significantly higher than previously reported results of 3%-10% [22][23][24][25][26]. The coexistence of HBsAg and antiHBs was regarded simply as superinfection with a different subtype of HBV [27].…”
Section: Discussioncontrasting
confidence: 62%
“…Therefore, routine screening for HBV in schizophrenia patients is advocated, and HBV as well as hepatitis A immunization is recommended. In this study, 38.1% of HBsAg-positive patients showed coexistence of HBsAb, which was significantly higher than previously reported results of 3%-10% [22][23][24][25][26]. The coexistence of HBsAg and antiHBs was regarded simply as superinfection with a different subtype of HBV [27].…”
Section: Discussioncontrasting
confidence: 62%
“…This was supported by the observation that coexistence of HBsAg and anti-HBs is correlated with increased nucleotide variability in key areas of the HBV genome (Chen et al, 2011). Current studies also indicated that the serological profile of these patients showed minimal HBV replication and active CHB despite the presence of anti-HBs at a protective level (Colson et al, 2007;Liu et al, 2012). Therefore, we did not investigate the relationship between the HBsAg+/ anti-HBs+ serological profiles and HBV replication in this study.…”
Section: Discussionmentioning
confidence: 78%
“…Further genotyping assays demonstrated that subgenotype C2 (108, 33.3%) was predominantly expressed in CHB patients positive for both HBsAg and anti-HBs. It has been reported that genotype C is the predominant HBV strains in Chinese HBsAg+/antiHBs+ patients (Liu et al, 2012). Moreover, the presence of genotype C has been suggested as an independent predictive factor of elevated ALT, which corresponds to liver damage and HBV reactivation (Chu and Liaw, 2007a).…”
Section: Discussionmentioning
confidence: 99%
“…The MHR, situated in a central region of the S gene, has been recognized as an important genetic element associated with virus infection issues, such as vaccine escape, failure of anti-viral treatment, and progress of chronic infection [19][20][21]. Chang et al reported that the rate of HBV S gene mutants in HBV DNA positive children increased gradually from 7.8% before the vaccination program to 19.6%, 28.1%, and 23.1% at 5, 10, and 15 years, respectively, after the start of the vaccination program in Taiwan [22].…”
Section: Discussionmentioning
confidence: 99%